The impacts of warming on the toxicity of carbon nanotubes in mussels. (March 2019) - Andrade, Madalena; De Marchi, Lucia; Pretti, Carlo; Chiellini, Federica; Morelli, Andrea; Figueira, Etelvina; Rocha, Rui J.M.; Soares, Amadeu M.V.M.; Freitas, Rosa
Abstract: With the increased production and research on nanoparticles, the presence of carbon nanotubes (CNTs) in aquatic systems is very likely to increase. Although it has been shown that CNTs may cause toxicity in marine organisms, to our knowledge, the possible impacts under global temperature increase is still unknown. For this reason, biochemical and physiological impacts induced in Mytilus galloprovincialis due to the presence of functionalized multi-walled CNTs (f-MWCNTs) and increased temperature were investigated in the present study. The mussels exposed to increased temperature alone presented higher metabolic capacity and expenditure of glycogen as an energy resource to fuel up defense mechanisms and thus preventing oxidative damage. Contrarily, organisms exposed to f-MWCNTs alone seemed not stressed enough to demonstrate differences in the metabolism capacity. Furthermore, f-MWCNTs seemed not able to significantly activate their antioxidant and biotransformation enzymes, which in turn may led to oxidative damage in the cells especially when organisms were exposed to a warmer temperature. In fact, at higher temperature, the antioxidant response of organisms exposed to f-MWCNTs was not effective and oxidative damage levels were observed. Nevertheless, no additive or synergetic effects were observed when mussels were exposed to both stressors simultaneously. Graphical abstract: Image 1 Highlights: Warming temperature increased the metabolic capacity of mussels. Under increased temperature mussels were able to avoid cellular damage. Oxidative stress was observed in the organisms exposed to carbon nanotubes. The combination of stressors did not show an additive effect.